PERISTIWA TAHKIM (POLEMIK PERSELISIHAN POLITIK DAN IMPLIKASINYA) - Ridho, Miftahur (Institut Ilmu Keislaman Zainul Hasan Genggong, 2019)
Abstract: Politics is the biggest source of Muslim division. Starting from a dispute that occurred between Ali bin Abi Talib and Muawiyah who wanted revenge for Uthman's death, a Siffin war broke out which was a new chapter in the history of the birth of sects which had their own political vision. There are two schools - even two tendencies which gave birth to many schools - which were born as an implication of the war, namely Shi'ah and Khawarij. Both of these streams emerge because of the same factor, namely extremity and contradiction. The appearance of the Khawarij gave a large share of the emergence and spread of Shi'ah. Extremity claims propagated by one of the streams above encourage the emergence of rival extremities from other schools. The struggle between the two schools gave rise to another stream which aimed to mediate between the two contradictory sides, namely Murji'ah, a school that dared to bring up its own vision, even though in the end one of the two firqahs was followed. In subsequent developments emerged the flow of Mu'tazilah, Qadariyyah and Jabbariyyah.Keywords: Politics, flow, theology